Lifestyle factors and disease‐specific differences in subgroups of Swedish Myasthenia Gravis. (4th October 2018) - Westerberg, Elisabet; Landtblom, Anne‐Marie; Punga, Anna Rostedt
Abstract: Purpose: To evaluate disease‐specific differences between Myasthenia Gravis (MG) subgroups and compare patterns of lifestyle between MG patients and population controls. Methods: All MG patients (n = 70) in Jönköping County, Sweden, were invited to answer a disease‐specific questionnaire, containing questions about disease‐specific data, lifestyle, comorbidity, and mental fatigue. The patients were clinically evaluated. Four hundred age‐ and gender‐matched population controls were invited to answer the nondisease‐specific part of the questionnaire. Disease‐specific issues were compared between MG subgroups. Lifestyle‐related factors and concomitant conditions were compared to the population controls. Results: Forty MG patients and 188 population controls participated in the study. In the late‐onset MG (LOMG; N = 18) subgroup, the male predominance was higher than previously reported. In the early‐onset MG (EOMG; N = 17) subgroup, time to diagnosis was longer, fatigue was higher, and bulbar weakness was the dominant symptom (65%). Compared to their matched population controls, LOMG patients were more obese (OR = 13.7, P = 0.015), ate less fish (OR = 4.1, P = 0.012), tended to smoke more (OR = 4.1, P = 0.086), and tended to be employed as manual laborers more often (OR = 2.82, P = 0.083). Mental health problems and sickness benefits were more common among MG patients than in controls, and MG patients were less regularly doing focused physical activity. Conclusions: It is important to consider disease‐specific differences when tailoring the management of individual MG patients. There is a need for improved knowledge on how to apply primary and secondary prevention measures to lifestyle disorders in MG patients without risk of deterioration.